2020
DOI: 10.3390/a13050113
|View full text |Cite
|
Sign up to set email alerts
|

Goal Oriented Time Adaptivity Using Local Error Estimates

Abstract: We consider initial value problems (IVPs) where we are interested in a quantity of interest (QoI) that is the integral in time of a functional of the solution. For these, we analyze goal oriented time adaptive methods that use only local error estimates. A local error estimate and timestep controller for step-wise contributions to the QoI are derived. We prove convergence of the error in the QoI for tolerance to zero under a controllability assumption. By analyzing global error propagation with respect to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…As can be seen in the numerical results in Section 8.3, this does not lead to a loss of order. Other options for constructing partitioned time‐integration methods based on SDIRK2 are discussed in [33, Chap. 5].…”
Section: Multirate Time Discretizationmentioning
confidence: 99%
“…As can be seen in the numerical results in Section 8.3, this does not lead to a loss of order. Other options for constructing partitioned time‐integration methods based on SDIRK2 are discussed in [33, Chap. 5].…”
Section: Multirate Time Discretizationmentioning
confidence: 99%
“…The accumulation of these errors, which we refer to as global errors, is more difficult to estimate and will not be considered in this paper. Studies considering the global errors can be found in reference [19]. We recall that the numerical solution at the time step n + 1 is calculated by ( 19)…”
Section: Error Estimatementioning
confidence: 99%
“…Noventa et al developed a similar time step adaptation strategy in unsteady incompressible turbulent flow simulations [21], which is further tested in compressible simulations focusing on the comparison of different step size controllers [22]. The adaptive method based on local temporal error was further developed for goal oriented time step adaptation and compared with a method based on global error estimate [19]. However, most of them such as, the studies in references [4,5,21,22], consider the temporal discretization methods separately as an ODE solver using the method of lines but do not take into account specific physical properties of the problem and specific spatial discretization adopted.…”
Section: Introductionmentioning
confidence: 99%
“…[6,14,20,15] and the references therein. One possible way to overcome this requires checkpoint techniques as presented in [19]. In this paper, we instead treat time as just another variable and perform an all-at-once discretization of the complete space-time cylinder 𝑄.…”
Section: Introductionmentioning
confidence: 99%